PENEGAKAN HUKUM TERHADAP IZIN KEPEMILIKAN SENJATA API BELA DIRI DI WILAYAH HUKUM POLDA RIAU - Rendi Fitrianda; Bagio Kadaryanto; Silm Oktapani (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The purpose of this study is to analyze law enforcement, obstacles, and efforts to overcome obstacles to self-defense firearm ownership permits in the jurisdiction of the Riau Regional Police, based on Republic of Indonesia National Police Regulation Number 1 of 2022. The method used is sociological legal research. Based on the research results, it is known that law enforcement regarding self-defense firearm ownership permits in the jurisdiction of the Riau Regional Police, based on Republic of Indonesia National Police Regulation Number 1 of 2022, is an implementation of Perpol No. 1 of 2022, which operates through several main patterns: strengthening administrative verification, increasing field supervision, taking action against owners who fail to renew their permits, and providing guidance to gun holders to understand their obligations and limitations on use. The author observed that some permit holders still do not fully comply with the permit renewal requirements and safe storage procedures. However, the Riau Regional Police actively conduct re-registration, administrative summonses, and physical inspections of weapons to ensure compliance. When violations are found, corrective action is taken through permit revocation, weapon confiscation, or transfer of the case to criminal proceedings if there are elements of a legal violation. Obstacles include weak compliance by owners in renewing permits, a lack of public understanding of administrative obligations, and limited field supervision due to a lack of personnel. Furthermore, the data collection and monitoring processes are not yet fully digitally integrated, making it difficult to track permit status quickly and accurately. Obstacles also arise from internal factors such as limited facilities, and external factors such as low legal awareness among owners, who tend to neglect permit renewals even after notification. Efforts include increasing direct outreach to firearm owners regarding licensing obligations, providing regular warnings through official information and communication systems, and tightening permit evaluation mechanisms with more intensive field verification.